SHM_1227491_HST_3D Four-Sided Stone Axe - National Historical Museums (National Historical Museums, 2026)
Structured light 3D model of a four-sided stone axe from the Swedish Neolithic, collected in the field from Lillerberg in Hallsberg paris, Närke, Sweden and held in the collections of the National Historical Museums in Stockholm.

Link to the Dynamic Collection platform

https://dyncoll.ht.lu.se/artifact_view.php?item=400

Link to Sök I Samlingarna

https://samlingar.shm.se/object/B0CD2D84-5C4E-40AB-A407-22700CFEC678
Keywords: Archaeology; Archaeology; Archaeology/history; History and archaeology; Structured Light Scanning; Swedish Neolithic; Marka; Dynamic Collections; 3D Model; Museum Object; History and Archaeology; Historia och arkeologi; Archaeology; Arkeologi